Impact characterisation of glass fibre-reinforced polymer (GFRP) Type C-600 and E-800 using a single stage gas gun (SSGG) - Safri, Syafiqah Nur Azrie; Hameed Sultan, Mohamed Thariq; Cardona, Francisco (Universiti Putra Malaysia Press, 2017)
This paper presents experimental findings derived from high velocity impact tests on woven-roving Glass Fibre-Reinforced Polymers (GFRP) Type E-800 g/m² and Type C-600 g/m². The effects on specimen thickness, projectile shape and gas gun pressure were investigated. As the gas gun pressure increases, there is a proportional increase in the projectile kinetic energy, the projectile initial velocity, the maximum force exerted on the specimens and in energy absorption upon impact. During the test, the shape of the projectile, the target thickness and the gas gun pressure significantly affected the impact performance of the GFRP. From the experiment, it was found that GFRP Type E-800 g/m² is stronger and more impact resistant compared with GFRP Type C-600 g/m², due to the fact that E-glass materials have higher fibre volume and density and overall better mechanical properties than C-glass fibres. Therefore, GFRP Type E-800 g/m² composites should be considered for applications in load and impact bearing aircraft structures.